THE IMPACT OF TRANSFORMATIONAL LEADERSHIP ON ACHIEVING ORGANIZATIONAL QUALITY: A SURVEY STUDY OF SELECTED HOSPITALS IN KARBALA - Hayder jabber jasim; Haider Ali Naji; Ali Lateef Oudah; Kamal Mohammed Yaqoob (Scholars Digest Publishing, 2025)
The current research aims to examine the role of transformational leadership, with its dimensions (idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration), in achieving organizational quality through its dimensions (organizational culture, top management commitment to quality, process quality, and service quality). The study seeks to answer key research questions, including: What is the impact of transformational leadership on enhancing organizational quality in a sample of hospitals in Karbala? A questionnaire was used as a measurement tool for the research variables, and the relationship between them was tested through a purposive sample comprising (50) administrative leaders (managers, their deputies, department heads, and administrative unit heads). Statistical methods from the (AMOS, V.25) and (SPSS, V.25) programs were employed. To achieve the research objectives, several main and sub-hypotheses were formulated to establish and test the relationship between the two variables in a field setting. The study results revealed several conclusions, the most significant of which is the existence of a direct impact of transformational leadership on organizational quality. Based on these findings, the study offers several recommendations, the most important being the need for hospital administrations under study to focus on transformational leadership and its dimensions, reinforcing its role at all management levels to support and enhance organizational quality.
Keywords: Transformational Leadership, Organizational Quality.